Nanopackaging : from nanomaterials to the atomic scale : Proceedings of the 1st International Workshop on Nanopackaging, Grenoble 27–28 June 2013 /: from nanomaterials to the atomic scale : Proceedings of the 1st International Workshop on Nanopackaging, Grenoble 27–28 June 2013. (2015) - Unknown
No abstract available